Advances in enzyme technology - Larroche, Christian; Pandey, Ashok; Singh, Ram Sarup; Singhania, Reeta Rani (Biomass, biofuels and biochemicals, 2019)
Biomass, Biofuels and Biochemicals: Advances in Enzyme Technology provides state-of-the-art information on the fundamental aspects and current perspectives in enzyme technology to graduate students, postgraduates and researchers working in industry and academia. The book provides information about the use of enzyme technology as an important tool for biotechnological processes, including food, feed, fuels, textiles, paper, energy and environmental applications. The search for improvements in existing enzyme-catalyzed processes dictates the need to update information on various enzyme technologies. The book gives a snapshot of current practice and research in the area of enzyme technology.